Improvement Efforts Student Learning Outcomes Using STAD Cooperative Model at SDN Keleyan 2 Class V - Virna Dwi Agustin; Saniyatus Safaah; Mita Tri Wahyuni (Journal of Action Research in Education, 2024)
This research aims to improve student learning outcomes in science subjects containing social science material through the STAD type cooperative learning model. This research is Classroom Action Research with a cycle model that is carried out repeatedly and continuously. The subjects of this research were 18 class V students consisting of 11 male students and 7 female students. The object of this research is student learning outcomes. Data collection methods are carried out through observation, tests and documentation. The data analysis technique was carried out descriptively, quantitatively and qualitatively. The research results show an increase in student learning outcomes. This can be seen from the average score at the pre-cycle stage, which is 60.00 and has a learning completeness of 22% and at the end of the first cycle the average score is 74.43 with learning completeness being 61% and at the end of the second cycle the average score -The average rose to 96.55 with learning completion reaching 100%. The target for achieving learning outcomes in this research is 70% of students getting a complete score, namely 65. Apart from increasing student learning outcomes, the learning process in the classroom has also improved.